Irigasi Way Tebu: Penguatan Agraria dalam Mewujudkan Sustainable Development Goals - Reni Royani; Nabila Maulidia; Rizky Juliantoro; Rinaldo Adi Pratama (Universitas Hamzanwadi, 2022)
Since the enactment of ethical politics during the reign of the Dutch East Indies, there has been development in the field of irrigation. The Dutch colonial government-built irrigation of Way Tebu Irrigation Canals. This research was conducted to reveal the development of Way Tebu irrigation which has an impact on agrarian development in realizing the Sustainable Development Goals (SDGs) for the Pringsewu community. The type of research used is qualitative. Strengthening the SDGs is important to be applied to the government sector, especially in the agrarian sector in order to ensure that point number one, namely Without Poverty and point two, namely Without Hunger, is achieved, in Pringsewu there is Way Tebu Irrigation whose existence is able to support the strengthening. The results of this study show that since the Dutch colonial era until now, the Way Tebu irrigation network has not undergone significant changes so that its authenticity is maintained. The Way Tebu Irrigation Network is the lifeblood of agriculture in Pringsewu and surrounding areas. Through this irrigation network, agricultural lands become fertile and fish farming is running well. The proceeds from commodities, in addition to being personally consumed by local farmers, are also traded to various regions through existing factories. The existence of the Way sugarcane irrigation canal is able to prosper the Pringsewu community and is able to realize Sustainable Development Goals for the Pringsewu community.